Impact of Self-Concept and Achievement Motivation on Academic Achievements of MBA Students: An Empirical Analysis - Rudranath, Polampati G. (Prabandhan: Indian Journal of Management, 2013)
The present investigation is the study of achievement motivation and self concept in relation to academic achievement of management students. The following are the nature of the variables studied. First, achievement motivation is the basis of achievement motive that is a motive to achieve. Second, self concept is the subjective perception of one’s self. Self concept is a multidimensional construct that refers to an individual’s perception of the self in relation to any number of characteristics such as academics, gender roles, sexuality, racial identity, personality, skills, abilities, occupations and hobbies, physical, psycho-social, and emotional characteristics. Third, academic achievement or performance is the outcome of education - the extent to which a student has achieved his/her educational goals. Academic achievement is commonly measured by examinations or continuous assessment. In educational institutions, academic achievement is measured by academic performance or how well a student meets the standards set out by the university and the concerned council. The study was conducted to identify whether there is any strong relationship among the two variables - Self-Concept and Achievement Motivation, and how these two variables impacted the performance of the students. In addition, these two variables were compared among the sample respondents (male and female students) to analyze how male and female students differed from each other with respect to the said two variables.